Identification of genes related to stress affecting thymus immune function in a chicken stress model using transcriptome analysis. (September 2021) - Tian, Huihui; Guo, Yujie; Ding, Mengxia; Su, Aru; Li, Wenting; Tian, Yadong; Li, Kui; Sun, Guirong; Jiang, Ruirui; Han, Ruili; Yan, Fengbin; Kang, Xiangtao
Abstract: With the rapid development of the poultry breeding industry and highly intensive production management, the losses caused by stress responses are becoming increasingly serious. To screen candidate genes related to chicken stress and provide a basis for future research on the molecular mechanisms governing the effects of stress on chicken immune function, we successfully constructed a chicken stress model by exogenously introducing corticosterone (CORT). RNA-seq technology was used to identify and analyze the mRNA and enrichment pathways of the thymus in the stress model group and the control group. The results showed that there were 101 significantly differentially expressed genes (SDEGs) ( P adj < 0.05, |log2fold changes| ≥ 1 and FPKM >1), of which 44 were upregulated genes, while 57 were downregulated genes. Gene Ontology (GO) enrichment analysis found that the terms related to immunity or stress mainly included antigen processing and presentation, positive regulation of T cell-mediated immunity, and immune effector process. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis showed that the main pathways related to immunity or stress were the PPAR signaling pathway, NOD-like receptor signaling pathway, and intestinal immune network for IgA production. Among the SDEGs, XCL1, HSPA8, DMB1 and BAG3 are strongly related to immunity or stress and may be important genes involved in regulating stress affecting the immune function of chickens. The above results provide a theoretical reference for subsequent research on the molecular regulatory mechanisms by which stress affects the immune function of poultry. Graphical abstract: Image 1 Highlights: It is theoretically feasible to construct a chicken stress model using exogenous CORT. It is theoretically feasible to construct a chicken stress model using exogenous CORT. In this study, a CORT-induced stress model was successfully constructed in 7-day-old Gushi chicken. A total of 101 CORT-induced thymus significantly differentially expressed genes (SDEGs) were obtained by RNA-seq. XCL1, HSPA8, DMB1 and BAG3 may be important genes involved in stress-induced immunoregulation of chicken.